Evaluation of serological assays for identification of parvovirus B19 immunoglobulin M. - Tolfvenstam, T (1996)
Three different enzyme immunoassays (EIAs) (Parvoscan-B19, IBL parvovirus B19, and IDEIA parvovirus B19) and one immunofluorescence assay (Biotrin Parvo B19 IFA) were evaluated for detection of parvovirus B19 immunoglobulin M (IgM) antibodies in 203 clinical serum samples. An IgM antibody capture radioimmunoassay was used as a reference test. Serum specimens obtained from patients with clinical symptoms suggestive of parvovirus B19 infections were used to evaluate the sensitivities of the assays, which were shown to be comparable for the Biotrin IFA and IDEIA (97%) and lower for the other two EIAs (90%). In order to test the specificity of the assays, clinical serum samples with IgM antibodies against other viruses were examined, as well as sera with rheumatoid factor activity and sera from healthy pregnant women. The specificities of B19 IgM antibody detection were 96% for the Biotrin IFA, 96% for IDEIA, 90% for Parvoscan, and 88% for the IBL assay. These results show that all four assays can be recommended for diagnostic purposes, although false-positive results may be seen with other acute viral infections, healthy pregnant women, and rheumatoid factor-positive samples.